Clinical assessment of position of impacted lower third molars and their indications for extraction (Mustansiria Dental Journal, 2018)
The purpose of this study was to assess the position of impacted lower thirdmolars, the indications for extraction, and the post-operative complications. Recordsof patients who attended Misan general hospital between March 2008 and April 2009for surgical removal of mandibular third molars.The angulation type and depth of impaction were determined by reviewing theorthopantomograms. A total of 140 impacted teeth were surgically extracted from 132patients (69 males, 63 females). The reasons for extraction include recurrentpericoronitis (55%) followed by caries (25%) and prophylactic purposes (20%).Mesioangular impactions accounted for (49.29 %) and Level 1 position ofimpaction accounted for (65%) of extractions. 40 complications (28.57%), includingpersistent pain and swelling, infection, dry socket, Trismus and ulceration werereported . Persistent pain and swelling was the most common complications followedby infection.There was no significant relationship between the angulation, level of impactionand the occurrence of complications. Mesioangular type and Level A position ofimpaction were the most common impaction. Although the association was notsignificant, high frequency of post-operative complications was observed inmesioangular, horizontal and level A position of impaction.